Fecal microbiota transplantation from young mice rejuvenates aged hematopoietic stem cells by suppressing inflammation - Zeng, Xiangjun; Li, Xiaoqing; Li, Xia; Wei, Cong; Shi, Ce; Hu, Kejia; Kong, Delin; Luo, Qian; Xu, Yulin; Shan, Wei; Zhang, Meng; Shi, Jimin; et al. (Blood, 2023)
•FMT from young mice restored lymphoid differentiative potential and improved the number and engraftment ability of aged HSCs.•Lachnospiraceae and tryptophan-associated metabolites could improve both the phenotype and the reconstitution capacity of HSCs in aged mice. [Display omitted] Hematopoietic stem cell (HSC) aging is accompanied by hematopoietic reconstitution dysfunction, including loss of regenerative and engraftment ability, myeloid differentiation bias, and elevated risks of hematopoietic malignancies. Gut microbiota, a key regulator of host health and immunity, has recently been reported to affect hematopoiesis. However, there is currently limited empirical evidence explaining the direct impact of gut microbiome on aging hematopoiesis. In this study, we performed fecal microbiota transplantation (FMT) from young mice to aged mice and observed a significant increment in lymphoid differentiation and decrease in myeloid differentiation in aged recipient mice. Furthermore, FMT from young mice rejuvenated aged HSCs with enhanced short-term and long-term hematopoietic repopulation capacity. Mechanistically, single-cell RNA sequencing deciphered that FMT from young mice mitigated inflammatory signals, upregulated the FoxO signaling pathway, and promoted lymphoid differentiation of HSCs during aging. Finally, integrated microbiome and metabolome analyses uncovered that FMT reshaped gut microbiota composition and metabolite landscape, and Lachnospiraceae and tryptophan-associated metabolites promoted the recovery of hematopoiesis and rejuvenated aged HSCs. Together, our study highlights the paramount importance of the gut microbiota in HSC aging and provides insights into therapeutic strategies for aging-related hematologic disorders. Current models view “inflamm-aging” as a driver of hematopoietic dysfunction in older individuals, and methods to rejuvenate hematopoiesis are highly sought. Zeng and colleagues investigated the effect of replacement of the aged intestinal microbiome with juvenile microbiota in murine models, remarkably demonstrating that fecal microbiota transplants reduce inflammation, restoring lymphoid differentiation and engraftment capacity of aged hematopoietic stem cells (HSCs). Further, the authors showed that metabolites of specific microbiota species improved the reconstitution capacity of HSCs in aged mice, challenging the field to explore ways to translate these insights into a clinically feasible therapy.